The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1155/2013/834572
|View full text |Cite
|
Sign up to set email alerts
|

Review of Nondestructive Testing Methods for Condition Monitoring of Concrete Structures

Abstract: The deterioration of concrete structures in the last few decades calls for effective methods for condition evaluation and maintenance. This resulted in development of several nondestructive testing (NDT) techniques for monitoring civil infrastructures. NDT methods have been used for more than three decades for monitoring concrete structures; now it has been recognized that NDT plays an important role in the condition monitoring of existing RC structures. NDT methods are known to be better to assess and evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(75 citation statements)
references
References 62 publications
(61 reference statements)
0
65
0
1
Order By: Relevance
“…The measurement of radiation is achieved by the thermal sensor of an infrared (IR) camera [4], presenting a large number of applications ranging from medical imaging [5] to infrastructure inspections [6]. It is important to note that, depending on the performance required, IRT can be combined with other NDT methods, as this would increase confidence, deepen the analysis and make the validation of the particular study results more robust [2]. For example, Solla et al [7] and Sfarra et al [8] combine the Ground Penetrating Radar (GPR) and optical and ultrasonic techniques with IRT, respectively.…”
Section: Theory Of Infrared Thermographymentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of radiation is achieved by the thermal sensor of an infrared (IR) camera [4], presenting a large number of applications ranging from medical imaging [5] to infrastructure inspections [6]. It is important to note that, depending on the performance required, IRT can be combined with other NDT methods, as this would increase confidence, deepen the analysis and make the validation of the particular study results more robust [2]. For example, Solla et al [7] and Sfarra et al [8] combine the Ground Penetrating Radar (GPR) and optical and ultrasonic techniques with IRT, respectively.…”
Section: Theory Of Infrared Thermographymentioning
confidence: 99%
“…For this purpose, it is fundamental to use the best methods of inspection, with continuous updates and improvements [2].…”
Section: Introductionmentioning
confidence: 99%
“…The drawbacks of AE include its inability to detect preexisting damage and its susceptibility to ambient noise [12].…”
Section: Multifunctional Cement Composites Enhanced With Carbon Nanotmentioning
confidence: 99%
“…Another application of the NDT technique also can be used in the assessment of water content and concrete quality as reported by Breysse et al [6]. Several available NDT methods developed and used in the last few decades have been reviewed [2,7,8] and they concluded that the NDT methods are known to be better for assessing and evaluating the condition of RC structures in practice. In other words, the NDT method plays an important role in the assessment of existing structures.…”
Section: Introductionmentioning
confidence: 99%